Dampak Perkembangan Podcast serta Penyebab Berkurangnya Peminat Radio Tradisional - Rambe, Ahmad Sampurna; Diva, Dwi Dini Farah; Wahyuni, Rizki Cahya; Nurizain, Ayu; Lubis, Sabila Husna; Sakinah, Nina Kurnia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of technology and information has been proven by the emergence of new media that is increasingly massive. One of them is podcasts, digital audio documents uploaded online to be shared with the public. Podcasts are considered an alternative to radio, and in 2016, Nielsen predicted that 2020 would be the beginning of a